PENGEMBANGAN PENILAIAN GURU TINGKAT MI/SD DALAM MENINGKATKAN HASIL BELAJAR SISWA (IAI Sunan Giri Trenggalek, 2025)
The key factor in determining success in learning is assessment, as it serves as the teacher’s process for making decisions regarding students’ academic achievement. Therefore, assessments need to be developed to become more systematic and valid. Monoton assessment instruments that are not based on students' developmental stages often eliminate crucial elements in learning, such as creativity capacity, critical thinking, and life skills competence. This research aims for educators to develop a more comprehensive and diverse assessment system, as well as constructive assessment and feedback processes, which are also becoming increasingly important aspects for facilitating more effective and efficient evaluations. Whereas this is study employs a library research method. Drawing on books, journal articles, and publications listed in the references. In this way, all available sources of information can be utilized optimally in generating ideas relevant to the research. The findings of this study on developing assessment at the elementary and madrasah ibtidaiyah (MI/SD) level highlight that teachers’ efforts to evaluate students should involve three types of assessment tools: cognitive, affective, and psychomotor aspects. Furthermore, the development of assessments at the MI/SD level can be advanced through competency-based evaluation, the integration of technology and the enhancement of teachers’ skills. As a result, the implementation of assessments can be carried out more systematically, efficiently and effectively